2016
DOI: 10.1186/s12889-016-3818-y
|View full text |Cite
|
Sign up to set email alerts
|

Food safety knowledge of undergraduate students at a Canadian university: results of an online survey

Abstract: BackgroundFoodborne diseases are an important public health issue, and young adults are an important demographic to target with food safety education. Our objective was to assess the food safety knowledge of undergraduate students at a Canadian university, to identify potential areas for such education.MethodsIn February 2015, we conducted an online survey of 485 undergraduate students at a university in Ontario, Canada. We assessed various food-related factors, including cooking frequency and prior food handl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
4
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 48 publications
7
40
4
1
Order By: Relevance
“…Second, participants indicated students want to know how to safely store foods and for how long, particularly leftovers. Storage and use of leftovers has implications beyond food safety; in a study of undergraduate students at a Canadian university, the majority thought leftovers need to be thrown out after 1–2 days (versus the recommended 3–4 days), potentially contributing to food waste and security issues. Third, the use of microwaves as an important target for food safety education for high‐school students as identified here is a concept that is not explicit in most food handler training materials.…”
Section: Discussionmentioning
confidence: 99%
“…Second, participants indicated students want to know how to safely store foods and for how long, particularly leftovers. Storage and use of leftovers has implications beyond food safety; in a study of undergraduate students at a Canadian university, the majority thought leftovers need to be thrown out after 1–2 days (versus the recommended 3–4 days), potentially contributing to food waste and security issues. Third, the use of microwaves as an important target for food safety education for high‐school students as identified here is a concept that is not explicit in most food handler training materials.…”
Section: Discussionmentioning
confidence: 99%
“…While in other studies mentioned the gender of men have a better knowledge than women in terms of food security (27,28). On the contrary, the activity related to food is mostly done by women who have lower knowledge.…”
Section: B Sexmentioning
confidence: 91%
“…Based on previous study, as the level of education increases with age, an increase in knowledge was observed, which contradicts with this study. 27 Though a positive significant association was observed between KAP among the respondents from various field of study, pharmacy students scored highest. This study observes students from healthcare background had much better KAP towards FS&H compared to non-health related courses.…”
Section: Association Of Kap Score Among Socio-demographic Factorsmentioning
confidence: 92%